Use of synthetic fibers in self-compacting lightweight aggregate concretes. (December 2015) - Corinaldesi, V.; Moriconi, G.
Abstract: In this work, fiber reinforced SCLWAC (self-compacting lightweight aggregate concrete) mixtures were studied, in which synthetic fibers were used. Eight different SCLWACs were prepared, in which, as aggregates, different combinations of fine and coarse expanded clay were tried, also partially replaced by either quartz sand or aggregate coming from concrete recycling. SCLWACs were characterized at the fresh state by means of slump flow, V-funnel and L-box tests, and after hardening by means of compression, splitting tension and bending tests, and drying shrinkage measurements. Strength class of LC 45/50 was obtained by using synthetic macrofibres when the oven dry density of SCLWAC was about 1600 kg/m 3, while if the oven dry density of SCLWAC was lower than 1250 kg/m 3 a strength class of LC 25/28 was reached as well. Tensile and flexural strength values were consistent with concrete strength class, while the elastic modulus was quite low with respect to normal weight self-compacting concrete (SCC). The post-cracking behavior of SCLWAC was strongly improved by the addition of synthetic macrofibers, which provided strain-hardening effect similar to that achievable by means of steel fibers, even if characterized by a sensibly lower weight. In conclusion, SCLWACs showed excellent combination of mechanical and functional properties. Highlights: Study of self-compacting lightweight aggregate concrete (SCLWAC). Use of synthetic macrofibers to obtain an improved post-cracking behaviour. Special concretes with excellent combination of mechanical & functional properties.